Can a pentamethylcyclopentadienyl ligand act as a proton-relay in f-element chemistry? Insights from a joint experimental/theoretical study. Issue 6 (23rd October 2014) - Kefalidis, Christos E.; Perrin, Lionel; Burns, Carol J.; Berg, David J.; Maron, Laurent; Andersen, Richard A.
Abstract : Isomerisation of buta-1, 2-diene to but-2-yne by (Me5 C5 )2 Yb is a thermodynamically favourable reaction, with the Δr G ° estimated from experimental data at 298 K to be −3.0 kcal mol −1 . Abstract : Isomerisation of buta-1, 2-diene to but-2-yne by (Me5 C5 )2 Yb is a thermodynamically favourable reaction, with the Δr G ° estimated from experimental data at 298 K to be −3.0 kcal mol −1 . It proceeds in hydrocarbon solvents with a pseudo first-order rate constant of 6.4 × 10 −6 s −1 and 7.4 × 10 −5 s −1 in C6 D12 and C6 D6, respectively, at 20 °C. This 1, 3-hydrogen shift is formally forbidden by symmetry and has to occur by an alternative pathway. The proposed mechanism for buta-1, 2-diene to but-2-yne isomerisation by (Me5 C5 )2 Yb involves coordination of methylallene (buta-1, 2-diene) to (Me5 C5 )2 Yb, and deprotonation of methylallene by one of the Me5 C5 ligands followed by protonation of the terminal methylallenyl carbon to yield the known coordination compound (Me5 C5 )2 Yb(η 2 -MeCCMe). Computationally, this mechanism is not initiated by a single electron transfer step, and the ytterbium retains its oxidation state (II) throughout the reactivity. Experimentally, the influence of the metal centre is discussed by comparison with the reaction of (Me5 C5 )2 Ca towards buta-1, 2-diene, and (Me5 C5 )2 Yb with ethylene. The mechanism by which the Me5 C5 acts as a proton-relay within the coordination sphere of a metal also rationalises the reactivity of (i) (Me5 C5 )2 Eu(OEt2 ) with phenylacetylene, (ii) (Me5 C5 )2 Yb(OEt2 ) with phenylphosphine and (iii) (Me5 C5 )2 U(NPh)2 with H2 to yield (Me5 C5 )2 U(HNPh)2 . In the latter case, the computed mechanism is the heterolytic activation of H2 by (Me5 C5 )2 U(NPh)2 to yield (Me5 C5 )2 U(H)(HNPh)(NPh), followed by a hydrogen transfer from uranium back to the imido nitrogen atom using one Me5 C5 ligand as a proton-relay. The overall mechanism by which hydrogen shifts using a pentamethylcyclopentadienyl ligand as a proton-relay is named Carambole in reference to carom billiards.